2021
DOI: 10.1098/rstb.2020.0021
|View full text |Cite
|
Sign up to set email alerts
|

Male partner participation in maternity care and social support for childbearing women: a discussion paper

Abstract: Male partners/fathers are key support persons for many childbearing women and their involvement in pregnancy, childbirth and the postpartum/postnatal period has beneficial effects on a wide range of outcomes related to maternal and child health and family wellbeing. Social support is implicated in the relevant causal pathway, but has received largely tangential attention in the public health literature. This discussion paper aims to reframe men's participation in maternity care as an opportunity to enhance the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 94 publications
0
16
1
4
Order By: Relevance
“…As Spry et al discuss in their piece [37], interventions promoting social support antenatally can reduce rates of depression postnatally. Although in our setting, partner support appeared to play a less significant role than perceived and received support, other studies have found that increasing partners' involvement in women's care can enhance support to women [38].…”
Section: Discussioncontrasting
confidence: 82%
“…As Spry et al discuss in their piece [37], interventions promoting social support antenatally can reduce rates of depression postnatally. Although in our setting, partner support appeared to play a less significant role than perceived and received support, other studies have found that increasing partners' involvement in women's care can enhance support to women [38].…”
Section: Discussioncontrasting
confidence: 82%
“…The percentage of respondents who answered that they received support from their husbands during pregnancy did not show any statistical significance but did show an increase compared to before the implementation of IEC activities. In developing countries, the male plays the role of the decision-maker in the household, thus being aware of when to actively support women during pregnancy or reacting sensitively to the women’s abnormal signal is important to the improvement of women’s health by increasing the use of prenatal medical services [ 23 , 24 , 25 , 26 ]. Therefore, previous studies are continuing research on methods to increase the participation of spouses and are actively trying to resolve negative factors.…”
Section: Discussionmentioning
confidence: 99%
“…Public health initiatives around maternal and child health in lower-and middle-income countries typically also assume a default nuclear family structure in which mothers are largely responsible for the health of their children-this excludes vital support structures such as grandmothers (see [92]). There are even some perceptions in global health that grandmothers are the 'guardians of tradition' [93] and that, if they have a role at all, it is a role that has the potential for negative maternal and health outcomes, given that the advice of older women may contradict that of public health professionals.…”
Section: What Are the Implications Of A Malementioning
confidence: 99%